2006
DOI: 10.1002/mrc.1745
|View full text |Cite
|
Sign up to set email alerts
|

Phase transition of L‐Ser monohydrate crystal studied by 13C solid‐state NMR

Abstract: We used gravimetric analysis (GA) and (13)C solid-state nuclear magnetic resonance (NMR) to study solid-phase transition from the transparent single crystal of L-serine (L-Ser) monohydrate to a turbid powder. We found that L-Ser monohydrate loses water molecules and transforms into an anhydrate, thus experimentally demonstrating Frey's assumption. Application of a handmade cross-polarization (CP) NMR probe with a saddle-type coil to the oriented crystal of the L-Ser monohydrate revealed the dehydration mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…29 On the other hand, the nuclear magnetic resonance spectra for the L-serine-coated ZnO samples showed peaks at 63.2 ppm and 56.1 ppm, corresponding to the C β and C α carbons in the amino acids. 28 These results again confirmed that the C, O, and N peaks in XPS were attributable to the coating agents and dispersants.…”
Section: Nuclear Magnetic Resonance Spectroscopysupporting
confidence: 63%
See 1 more Smart Citation
“…29 On the other hand, the nuclear magnetic resonance spectra for the L-serine-coated ZnO samples showed peaks at 63.2 ppm and 56.1 ppm, corresponding to the C β and C α carbons in the amino acids. 28 These results again confirmed that the C, O, and N peaks in XPS were attributable to the coating agents and dispersants.…”
Section: Nuclear Magnetic Resonance Spectroscopysupporting
confidence: 63%
“…All four types of coated ZnO nanoparticles showed δ 11 (COO -) and δ 22 (COO -) peaks, and these were attributed to the carboxylates in citrate and L-serine. 27,28 In the citrate-coated ZnO nanoparticles, the characteristic peak of the quaternary 30 40 2θ ( carbon (C q ) of citrate was found at 76.6 ppm, and C 1 , C 2 , C 3 , C 4 , and C 5 peaks originating from HEPES were observed in the range of 50-60 ppm ( Figure 4A-C). 29 On the other hand, the nuclear magnetic resonance spectra for the L-serine-coated ZnO samples showed peaks at 63.2 ppm and 56.1 ppm, corresponding to the C β and C α carbons in the amino acids.…”
Section: Nuclear Magnetic Resonance Spectroscopymentioning
confidence: 99%
“…Grafting was originally introduced as an alternative to the traditional mineral weighting technique (tin-phosphate-silicate weighting), a method used for decades to increase silk weight in order to compensate for the loss resulting from degumming. [3] However, in recent years grafting has been regarded not only as an effective treatment for increasing silk weight but also as a powerful Summary: By using DSC, 13 C CP/MAS NMR and SEM, we studied the physical properties and chemical structure of silk fibers grafted with methacrylamide (MAA). At a given MAA concentration, the inverse of fiber weight gain linearly increased with increasing square root of the initiator concentration, and at a given initiator concentration the fiber weight gain increased with increasing MAA concentration.…”
Section: Introductionmentioning
confidence: 99%
“…At a given MAA concentration, the inverse of fiber weight gain linearly increased with increasing square root of the initiator concentration, and at a given initiator concentration the fiber weight gain increased with increasing MAA concentration. 13 C CP/ MAS NMR demonstrated that the primary and secondary structure remained unchanged, regardless of MAA grafting, implying the poor compatibility and the lack of new additional hydrogen bonding between the silk fiber and the MAA graft polymer. The degree of grafting in MAA-grafted silk fiber (the accurate amount of actually loaded MAA polymer within the fiber matrix) can be evaluated from determination of the ratio of heat capacities calculated from two individual endothermic DSC peaks of silk fibroin and MAA polymer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation